TOWARDS SUSTAINABLE CITIZENSHIP BEHAVIOR: THE LITERATURE STUDY FOR SUSTAINABLE ENTREPRENEURSHIP EDUCATION - Nuringsih, Kartika; Maupa, Haris; Taba, Muhammad Idrus (International Journal of Application on Economics and Business, 2024)
In line with the sustainable development goals (SDGs), the entrepreneurial development model improves sustainability through sustainable entrepreneurship. The targeted segment to understand sustainability issues is entrepreneurs because their activities exacerbate the risk to environmental sustainability. Thus, the target achieved is community behavior towards sustainable development so that the emphasis of this concept is in the scope of citizenship behavior to build awareness of sustainable development. Therefore, a model was developed to foster sustainable entrepreneurial citizenship behavior (SECBs) among candidate entrepreneurs in Kulon Progo region, Daerah Istimewa Yogyakarta. This research is designed as a literature study that involves journals and articles in constructing the research model in line with sustainability issues. It involves seven constructs e.g., regional government support, sustainability entrepreneurial orientation, sustainability value, sustainability attitude, recognize opportunity, sustainable entrepreneurial intention, and SECBs. Totally 56 indicators are identified as tools for measuring seven constructs which will be followed up as instruments in the next study. The result serves as a foundation for the next study and information in developing entrepreneurship education. It relates to achieving the SDGs-4 in ensuring quality education and SDGs-8 in fostering decent work and economic growth.